2018
DOI: 10.1016/j.radonc.2017.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Photon vs. proton radiochemotherapy: Effects on brain tissue volume and perfusion

Abstract: Our results show that the tissue volume decrease depends on radiation dose delivered to the healthy hemisphere and differs between treatment modalities. In contrast, the decrease in perfusion was comparable for both irradiation modalities. We conclude that proton therapy may reduce brain-volume loss when compared to photon therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 39 publications
(45 reference statements)
4
39
2
Order By: Relevance
“…To the best of our knowledge, we are the first to report a perfusion decrease independent of radiation dose in GM using DSC. Several publications have shown that grey matter volume decreases after fractionated radiotherapy increasing with radiation dose 46 , 47 , 48 , 49 , since both CBV and CBF are tissue volume dependent parameters, we believe that the dose-independency found in grey matter is a result of decreased grey matter volume instead of an actual response in CBV and CBF independent on radiation dose given.…”
Section: Discussionmentioning
confidence: 68%
“…To the best of our knowledge, we are the first to report a perfusion decrease independent of radiation dose in GM using DSC. Several publications have shown that grey matter volume decreases after fractionated radiotherapy increasing with radiation dose 46 , 47 , 48 , 49 , since both CBV and CBF are tissue volume dependent parameters, we believe that the dose-independency found in grey matter is a result of decreased grey matter volume instead of an actual response in CBV and CBF independent on radiation dose given.…”
Section: Discussionmentioning
confidence: 68%
“…The first time point is used as a reference for both within- and between-subject registration. However, this requires further validation in the presence of large brain deformations between sessions, such as tumors, resections, or infarcts (Petr et al 2018).…”
Section: Theory: Implementationmentioning
confidence: 99%
“…Instead in some studies, GM volume is used as a covariate in the statistical analysis (Chen et al 2011). Note that while PVC, in theory, corrects only for the PV effects and takes into account the intra- and inter-subject variability of the GM-WM CBF ratio, GM covariation can additionally affect the estimated physiological correlation between GM CBF and GM volume (Petr et al 2018).…”
Section: Theory: Implementationmentioning
confidence: 99%
“…Patient's age at the preoperative period and tumor location are some of the current factors that determine the prognosis. In adult age groups, the incidence of high-grade glial tumors increases (3)(4)(5). Advanced age, especially over 70, is seen as a sign of poor prognosis.…”
Section: Introductionmentioning
confidence: 99%